Factors Influencing Ready-To-Eat Meal Consumer’s Intention To Use Food Delivery Apps During The Covid-19 Pandemic - Putri, Aisya Nadya; Rita Nurmalina; Suprehatin (Jurnal Manajemen dan Agribisnis, 2023)
Food delivery apps (FDA) are one of the most popular types of online marketing media, providing convenience for consumers to order ready-to-eat meals. The possibility of using and ordering food through FDA has also increased with the rise of Covid-19 cases as people practice social-distancing as a form of subjective norm. This study aims to analyze factors influencing consumers’ intention to use FDA during the pandemic. The primary data from online survey of 327 greater Jakarta residents who previously have or have not used FDA was analyzed using structural equation modelling. Factors significantly related to intention of the theory of reasoned action (TRA), technology acceptance model (TAM), trustworthiness, and perceived risk integration were subjective norm, perceived risk, and attitude, while other variables with significant direct effects were: (1) subjective norm and perceived risk towards attitude and (2) perceived ease of use towards attitude, perceived usefulness, and trustworthiness. Attitude were found moderating the relationship between subjective norms, perceived ease of use, and perceived risk with intention. TRA as a constituent theory was found to be the best at describing purchasing intention through FDA. Managerial implications for third-party FDA and partner restaurants were formulated from these findings.Keywords: consumer intention, food delivery apps, technology acceptance model (TAM), theory of reasoned action (TRA), ready-to-eat meal marketing